Hubungan Pekerjaan dan Pendidikan dengan Kejadian TB Paru di Kota Kupang - Ni Putu Ayu Natalia Dewi; Ni Made Susilawati (Inovasi Kesehatan Global, 2024)
Tuberculosis is an infection disease caused by Mycobacterium tuberculosis and most often infects the lungs. Pulmonary TB cases in Indonesia are the third largest in the world. NTT province occupies the 15th position out of 34th in Indonesia. Kupang city ranks first with the highest incidence of pulmonary TB in NTT. One of the factors that influence pulmonary TB is occupation and education level. This study aims to determine the differences in pulmonary TB incidence based on occupation and education level in Kupang City in 2021. This research was conducted at a health center in Kupang City, experimentally with a cross-sectional design, from March until May 2022. The research sample is secondary data of pulmonary TB patients with a total sample of 395 cases with a sampling technique that is total sampling. The result showed that there was no difference in the incidence of pulmonary TB based on occupation where p = 0,958 (p > 0,05) and there was a difference based on education level where p = 0,048 (p< 0,05). Further research is conducted to strengthen the effect of work and education level on the incidence of pulmonary TB. Keywords: ,